Factor Analysis Retaled to the Incident Reporting of Patient Safety Incident - Jenita, Albina; Arief, Yuni Sufyanti; Misbahatul, Eka (Fundamental and Management Nursing Journal, 2019)
Introduction: The Patient Safety Incidence (PSIs) is still a major problem in hospitals and each incident needs to be properly recorded and reported. The purpose of this study was to analyze the factors associated with the reporting of patient safety incidents to nurses based on Kopelman's Theory approach.Method: Analytical descriptive research design with Cross-sectional approach. The population of all nurses and obtained samples of 121 nurses were taken using cluster random sampling. Independent variables were knowledge, motivation, rewards, training, and feedback. The dependent variable was the reporting of patient safety incidents. The instrument uses questionnaires and observations with logistic regression test analysis.Result: There was a relationship between rewards (p = 0.011), training (p = 0.007) and feedback (p = 0.030) with reporting patient safety incidents. But there was no relationship between knowledge and motivation with reporting of patient safety incidents.Conclusion: Increasing rewards, training, and feedback are things that influence PSIs reporting. So that management support in PSIs reporting is needed to improve the quality of services in hospitals.